Structural Effects in the Recognition of DNA by Circular Oligonucleotides - Prakash, Gautam (J Am Chem Soc, 1992)
It was recently reported that certain pyrimidine-rich circular DNA oligomers can bind strongly and specifically to purine-rich DNA or RNA strands by forming bimolecular triple helical complexes.(1–3) In this study are investigated the effects of structural variations on the strength of binding for this new class of nucleotide-binding ligand. The number of loop nucleotides (nt) which is optimum for bridging the two binding domains of a circle is examined. Comparing loop sizes of 3, 4, 5, 6, and 10 nt, the optimum number of nucleotides in a loop is found to be five for the sequences studied. In order to test the method of construction and the ability of these compounds to bind sites of varied length, we attempted to synthesize circles of varied size. Circles over the size range 24–46 nt were successfully constructed. Varying the target site length shows that oligomers of four, eight, twelve, and eighteen nucleotides can be complexed strongly by circles, with melting temperatures (T(m)) 17° to >33 °C higher at pH 7.0 than the corresponding Watson–Crick duplexes of the same length. Also studied is the effect of the covalently closed circular structure in comparison to linear oligomers having the same sequence; it is shown that a covalently closed circle has considerably higher binding affinity than do three different “nicked” circles (linear oligomers) which contain the same bases. The high binding affinities of these circles are thus attributed to the entropic benefit of preorganization. Finally, the ability of such circles to bind to complementary sites within longer oligomers, the ends of which must pass beyond the loops of a circle, is confirmed by melting studies with synthetic target strands 36 bases in length.